Hubungan Intensitas Kebisingan Dengan Kelelahan Kerja Pada Pekerja di Pabrik Kelapa Sawit (PKS) PT. X Rokan Hulu - Hidayatul Fitria; Alfira Fitradika; Donny Haryxon; Sri Marhaeni (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Background: Fatigue is a process of decreased work performance, work efficiency, and reduced physical strength or endurance to continue activities or work. Data from the International Labor Organization (ILO) in 2012 states that every year 2.3 million people die due to disease or work accidents. In a day there are 847 cases of work accidents, of which around 36% of work accidents that occur are caused by fatigue. Several factors cause fatigue, including environmental factors, namely noise and lighting. The impacts of work fatigue include decreased motivation, and performance, low productivity, work errors, work-related illnesses, and work accidents. Based on initial information from several workers at POM PT. X, it is known that some workers claim to be tired at work. Objective: To determine the relationship between noise intensity and work fatigue in workers at POM PT. X Rokan Hulu 2020.Method: Analytical observational research with a cross-sectional approach, sample of 135 people. The sampling technique was carried out by total sampling which was tested statistically using the chi-square test. Results: There is a relationship between noise intensity and work fatigue (p-value = 0.022).